The Effect of Cryogenic Treatment Temperature on the Mechanical Properties and Microstructure of 440C Martensitic Stainless Steel - Indah Uswatun Hasanah; A. Ali Alhamidi; Rachmat Suryana (Universitas Sultan Ageng Tirtayasa, 2023)
The use of stainless steel worldwide is increasing due to its favorable mechanical properties, such as high hardness, corrosion resistance, and wear. One of the martensitic stainless steels is SS 440C. One of the main effects of increasing the significant carbon content is lowering the final martensitic temperature (MF) of the steel. If this temperature is below room temperature, the quenching process leaves austenite in the microstructure. This is commonly known as retained austenite (RA). In general, minimizing the number of RAs is recommended, as they can cause excessive wear. Therefore, the aim this research is for reduce the retained austenite content in SS 440C steel with a cryogenic treatment process. The cryogenic treatment was carried out for 50 minutes at temperatures of -80, -110, and -140°C and compared with non-cryogenic treatment to determine the residual austenite, hardness, and wear resistance. The highest hardness and wear resistance values were obtained from cryogenic treatment at -140°C at 58 HRC and 2.2 x 10-3 mm3/m. The metallographic results produce a martensite microstructure, residual austenite, and carbide phases. XRD analysis on cryogenic treatment samples at -140°C yielded structures of iron bcc, iron fcc, M7C3, and M23C6 compounds.